Literature Analysis of Arabic Language Evaluation Instrument Strategies and Designs in the Context of CBT - muhammad jundi robbany; Erlina Erlina; Umi hijriyah (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
The development of digital technology encourages innovation in learning evaluation systems, including in Arabic language subjects. The use of Computer Based Test (CBT) is considered more efficient, adaptive, and in accordance with the needs of the times. However, CBT-based Arabic language evaluation instruments still face challenges in their design and implementation strategies, especially in accommodating the four language skills of the language as a whole. This study aims to analyze the strategy and design of CBT-based Arabic language evaluation instruments through a systematic literature review. The study reviewed a number of national and international scientific articles in the last decade relevant to the topic. The results of the analysis show that most instruments are still focused on receptive skills with limited question formats, and have not fully met the principles of validity and fairness of digital access. This study recommends the development of instruments based on constructive alignment, interactive media integration, and authentic assessment. The findings are expected to be theoretical and practical in improving the quality of CBT-based Arabic learning evaluation. Key words: learning evaluation, Arabic language, CBT, instrument design, literature